Effect of Calcination Time on the Physicochemical Properties and Photocatalytic Performance of Carbon and Nitrogen Co-Doped TiO2 Nanoparticles; Catalysts; Vol. 10, iss. 8 - Massima M. E. S. Mouele Emile Salomon; Dinu M. Mihaela; Cummings F. Franscious; Fatoba O. O. Ojo; Zar Myint M. T. Myo Tay; Kyaw H. H. Htet Htet; Parau A. C. Anca Constantina; Vladesku A. Alina (2020, 2020)
Title screen